(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2023)
In 19th century Denmark, a sickly aristocrat rots his body and inherited land away as he obsesses over economic theory. One day, however, he attends a ballet show and becomes intrigued by one of the dancers and how she wavers when she lands on stage. He eventually meets her and becomes friends with her and remains intrigued by her odd behavior. The dancer shows him a way of living that embraces work and living in accordance with the wild which leads him to abandon his book and embrace a folk lifestyle. For additional context, watch the author’s reflection on the piece below.